O ensino aprendizagem de música no Musical Wicked - Scandar, Mariana Faria (2018)
Music in school is a recurring theme in the field of education and yet music education is not part of the curriculum. This research reflects a case study about a musical play performed at Colégio Cenecista Dr. José Ferreira, in Uberaba, state of Minas Gerais.The purpose of this study is to understand how the music teaching and learning took place through the process of the “Wicked” musical production (preparation and presentation), between February and August of 2017 in the above mentioned school. This research has at its core the fundamental theory that music teaching and learning is a social practice, and seeks to understand the complexities of the relationships involved in the practice, therefore showing that musical knowledge acquisition is connected to a plethora of social, environmental, and emotional issues. Furthermore, this research has led to the conclusion that musical theater can be a powerful tool in the teaching learning of music.